2000
DOI: 10.1073/pnas.240455697
|View full text |Cite
|
Sign up to set email alerts
|

Apical sorting of a voltage- and Ca 2+ -activated K + channel α-subunit in Madin-Darby canine kidney cells is independent of N-glycosylation

Abstract: The voltage-and Ca 2؉ -activated K ؉ (KV,Ca) channel is expressed in a variety of polarized epithelial cells seemingly displaying a tissuedependent apical-to-basolateral regionalization, as revealed by electrophysiology. Using domain-specific biotinylation and immunofluorescence we show that the human channel KV,Ca ␣-subunit (human Slowpoke channel, hSlo) is predominantly found in the apical plasma membrane domain of permanently transfected Madin-Darby canine kidney cells. Both the wild-type and a mutant hSlo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
89
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 100 publications
(95 citation statements)
references
References 60 publications
(94 reference statements)
5
89
1
Order By: Relevance
“…2 and 4. Bravo-Zehnder et al (45) also reported that myc-tagged MaxiK channel has characteristics similar to those of wild type. N terminus GFP tagging of hslo changes the channel's electrophysiological properties (46).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…2 and 4. Bravo-Zehnder et al (45) also reported that myc-tagged MaxiK channel has characteristics similar to those of wild type. N terminus GFP tagging of hslo changes the channel's electrophysiological properties (46).…”
Section: Discussionmentioning
confidence: 91%
“…Using single channel patch recording, currents from MaxiK channels were recorded at apical or basolateral membranes of different cell types (23, 56 -63). Bravo-Zehnder et al (45) reported that when transfected into Madin-Darby canine kidney cells, hslo protein traffics to the apical membrane. Endogenous rabbit MaxiK channel localizes at the apical membranes of collapsed thick ascending limb of the loop of Henle, as shown using indirect immunofluorescence microscopy (12).…”
Section: Discussionmentioning
confidence: 99%
“…Transfections with GtsO45 and G-EGFRc cDNAs were made using the LipofectAMINE Plus (Invitrogen) method according to the manufacturer's protocol, and permanent transformants were obtained after 2 weeks of selection with G418 (0.8 mg/ml) (Invitrogen) (49,50). Protein expression was induced by 10 mM sodium butyrate (49,50) at the restrictive temperature of 40°C for 20 h to accumulate the model proteins in the ER.…”
Section: Methodsmentioning
confidence: 99%
“…Domain-specific Biotinylation and Immunoprecipitation-Domainspecific biotinylation was made in MDCK cells cultured in Transwell chambers (49). The cells were washed twice in ice-cold PBS supplemented with 0.1 mM CaCl 2 and 1 mM MgCl 2 (PBS-CM), and then sulfo-NHS-biotin was added to a final concentration of 0.5 mg/ml for 60 min.…”
Section: Methodsmentioning
confidence: 99%
“…5, G and H). The hSlo1 intracellular carboxyl-terminal end is known to play a role in Slo1 surface expression (33)(34)(35). The 1007 YNMLCFGIY 1015 sequence has several important features that may explain why its absence causes channel trapping inside the cell: (i) it has a di-hydrophobic motif (underlined), which may act as endoplasmic reticulum export signal (36), (ii) it has a targeting tyrosinebased motif YXX (bold; X, any amino acid and , hydrophobic residue), which is a general sorting sequence that directs proteins to various cellular compartments, including the plasma membrane (37), and (iii) it is located in a strategic position near another two sequences containing di-hydrophobic motifs, 996 YGKDFCKALK 1005 (in hSlo1, amino acids KD are replaced with DL, which add another dihydrophobic motif and a tyrosine-based motif) and 1047 DLIFCL 1052 , whose deletion is sufficient to prevent current development (38) and protein surface expression (35), respectively.…”
Section: Association Of Slo1 Protein With Caveolin-1 In Native Aorticmentioning
confidence: 99%